Chalcidid parasitoids (Hymenoptera: Chalcididae) of Opisina arenosella (Walker) (Lepidoptera: Xyloryctidae) on coconut palm in southern India - Binoy, C.; Nivetha, S.; Arulprakash, R. (Zootaxa, 2024)
Eleven chalcidid pupal parasitoids (Hymenoptera: Chalcididae) of the black headed caterpillar (BHC), Opisina arenosella Walker, 1864 (Lepidoptera: Xyloryctidae) were reared from the South Indian states of Karnataka, Kerala and Tamil Nadu. Antrocephalus lugubris (Masi, 1932), Haltichella macrocera (Waterston, 1922) and Kriechbaumerella destructor (Waterston, 1922) are newly reported as parasitoids of BHC pupae. Also reported are A. hakonensis (Ashmead, 1904), A. phaeospilus Waterston, 1922, Brachymeria atteviae Joseph Narendran & Joy, 1972, B. megaspila (Cameron, 1907), B. nephantidis Gahan, 1930, B. nosatoi Habu, 1966, B. podagrica (Fabricius, 1787), and Psilochalcis carinigena (Cameron, 1907). Diagnoses, illustrations and new distributional data given for the 11 species and they are keyed together with six other chalcidid species known to be parasitoids of O. arenosella.